Rippling effect of corporate governance and corporate social responsibility synergy on firm performance: The mediating role of corporate image - Klenam Korbla Ledi; Enya Ameza – Xemalordzo (Cogent Business & Management, 2023)
There is a lack of consensus on how corporate governance and CSR relationships manifest across different institutional contexts especially within emerging economies, despite the wealth of available studies on the two concepts. The purpose of this study is to examine the relationship between corporate governance and corporate social responsibility as well as their effect on the performance of manufacturing firms via corporate image. The quantitative approach was used to collect data from a sample of 328 top executives of selected manufacturing firms in Ghana using the purposive sampling technique. The data collected was analyzed using AMOS and Process Macro. The study found that corporate governance has a high tendency to catalyze corporate social responsibility performance. The study further revealed that good corporate governance practices enhance both corporate image and performance of firms. Corporate social responsibility was also found to have a significant positive relationship with both corporate image and performance of manufacturing firms. The study further illuminated that corporate governance and corporate social responsibility have an indirect effect on firm performance through corporate image. The study has demonstrated how corporate governance and corporate social responsibility synergistically impact the performance of manufacturing firms. The study helps advance knowledge on the synergy and convergence of CSR and corporate governance interfaces and offers rich insight into the corporate governance and CSR puzzles within the context of the emerging economy.
Keywords: 650; corporate governance; corporate image; corporate social responsibility; firm performance; manufacturing